Alternative systems for poultry : health, welfare and productivity [ - Hocking, P. M. [ (Paul M.)]; Sandilands, Victoria (Poultry science symposium series, 2012)
Recent interest in how poultry are housed and managed in order to ensure profitability, sustainability, and good levels of animal welfare, are challenging issues that commercial poultry keepers face, particularly where legislation is bringing about lega requirements for housing. This book compares and contrasts alternative housing with conventional and traditional systems for commercial poultry (laying hens, meat chickens, turkeys, waterfowl and gamebirds) with regards to welfare, disease,health, nutrition, sustainability and genotype-environment interaction. It is suitable for researchers and students in poultry science and production and related subjects